GAMBARAN SANITASI SEKOLAH DASAR DI WILAYAH KERJA PUSKESMAS BANJARNEGARA 1 KECAMATAN BANJARNEGARA - Dwi Atin Faidah; Fany Ngudi Rohmawati (Unit Penelitian dan Pengabdian Masyarakat Politeknik Banjarnegara, 2024)
School is an institution that has an educational role so it needs to be supported by healthy sanitation conditions. Healthy sanitation conditions will have a major influence on the health level of the school students concerned. Problems that are still often encountered during school sanitation inspections are the condition of toilet facilities that do not meet the requirements such as slippery floors, no soap available and insufficient lighting. The aims of this research is to determine the description of primary school sanitation in the working area of ​​the Banjarnegara 1 Public Health Center in 2022. This study uses a descriptive research study. The population of this study is the total number of primary schools in the working area of ​​the Banjarnegara Health Center 1, namely 23 elementary schools. The research sample used a total sampling technique. The research instrument is a checklist. Data collection techniques are observation, measurement in elementary schools and interviews. The data analysis technique used is univariate analysis. The variables in this study are water, air, food, facilities and buildings, vectors and disease-carrying animals. The results of this study indicate that the condition of the water media (100%), the condition of the air media variable (52.20%), the condition of the food media (70%), the conditions of the facilities and building media (43.50%), the conditions of vectors and carrier animals disease (100%) meets the requirement. Suggestions for the school to providing lights for classes where lighting is still lacking, planting trees to reduce noise, providing closed organic and inorganic trash cans in each classroom and increase awareness for students to take an active role in maintaining school cleanliness, especially environmental cleanliness, waste disposal behavior and school latrine hygiene.